2004
DOI: 10.1161/01.hyp.0000107777.91185.89
|View full text |Cite
|
Sign up to set email alerts
|

Ac-SDKP Reverses Inflammation and Fibrosis in Rats With Heart Failure After Myocardial Infarction

Abstract: Abstract-Inflammation may play an important role in the pathogenesis of cardiac fibrosis in heart failure (HF) after myocardial infarction (MI). N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) is a naturally occurring antifibrotic peptide whose plasma concentration is increased 4-to 5-fold by angiotensin-converting enzyme inhibitors. We tested the hypothesis that in rats with HF after MI, Ac-SDKP acts as an anti-inflammatory cytokine, preventing and also reversing cardiac fibrosis in the noninfarcted area (rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 57 publications
8
122
0
Order By: Relevance
“…In previous in vivo studies, there is convincing evidence that Ac-SDKP, administered chronically in rat models of hyper- tension and myocardial infarction, prevented interstitial collagen deposition (4,16) by decreasing the interstitial cell proliferation, monocyte/macrophage infiltration and TGF-ß1 expression. Lin et al (17) reported that Ac-SDKP has an aortic antifibrotic effect due to a reduced expression of the profibrotic cytokine TGF-ß1 in the ANG II-induced hypertension rat model and that long-term Ac-SDKP treatment (18) and to suppress DNA and collagen synthesis in cardiac fibroblasts.…”
Section: Discussionmentioning
confidence: 89%
“…In previous in vivo studies, there is convincing evidence that Ac-SDKP, administered chronically in rat models of hyper- tension and myocardial infarction, prevented interstitial collagen deposition (4,16) by decreasing the interstitial cell proliferation, monocyte/macrophage infiltration and TGF-ß1 expression. Lin et al (17) reported that Ac-SDKP has an aortic antifibrotic effect due to a reduced expression of the profibrotic cytokine TGF-ß1 in the ANG II-induced hypertension rat model and that long-term Ac-SDKP treatment (18) and to suppress DNA and collagen synthesis in cardiac fibroblasts.…”
Section: Discussionmentioning
confidence: 89%
“…Similar hopes are associated with Ac-SD-KP [19]. This peptide is so short that synthesizing it under laboratory conditions is relatively uncomplicated and not very expensive, which is an additional, unquestionable advantage.…”
Section: Therapeutic Potential Of Tβ4mentioning
confidence: 81%
“…On the other hand, the experimental data supports the thesis about the potential therapeutic properties of Tβ4 and derivatives of this peptide-sulfoxide and Ac-SDKP. These molecules are considered to be a potential factor applicable in the treatment of cardiovascular diseases, corneal and skin wounds and brain injuries [19,20,22,28]. Based on an understanding the numerous activities of Tβ4, it is postulated that the peptide will be used in the treatment of, inter alia, myocardial infarction, chronic heart failure, diabetes, lupus, stroke, multiple sclerosis, pressure ulcers, burns, dry eye, viral infections and septic shock [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although angiotensin I is a good substrate for both of the two catalytic sites of ACE, other peptide substrates show distinct preferences for only one of the ACE catalytic sites. An example is the ACE substrate acetyl-SDKP that has been implicated as an antifibrotic and a bone marrow-suppressive peptide (14,15). Acetyl-SDKP is effectively hydrolyzed only by the N-terminal catalytic domain of ACE; ACE inhibition is associated with an elevation in blood levels of this peptide (16).…”
Section: Knockout Mice: Advantages and Disadvantagesmentioning
confidence: 99%